A membrane filter method for correlating colposcopic, histological, and cytological pictures: The application to nuclear DNA measurements. Issue 7 (July 1974) - Burn, G. P.; Singer, A.; Spriggs, A. I.
Abstract : A method is described for collecting cells on membrane filters in their natural topographical relationships, so that they can be correlated with exact areas in the cervix and with punch biopsy specimens. The same cell sample, after study with Papanicolaou stain, can then be used for other methods without the cells losing their spatial relationships. An example is given of an early cervical carcinoma in which, using a photographic method with a simple type of photometric device, the nuclear DNA was measured from accurately identified normal and neoplastic areas.